PALM OIL FARMERS' PERCEPTION ON THE IMPACT OF FARM ROADS DEVELOPMENT IN BENGKULU SELATAN REGENCY - Hermansyah, Deden; Sukiyono, Ketut; Romdhon, M. Mustopa (Journal of Agri Socio Economics and Business, 2025)
The agricultural sector plays a vital role in Indonesia’s economy but faces challenges such as limited infrastructure and low technology adoption, affecting efficiency and productivity. Road infrastructure is crucial for facilitating the distribution of palm oil from plantations to markets. This study analyzes the palm oil farmers’ perceptions on the farm road development and its impact on production management in Bengkulu Selatan. Research questions focus on how farmers assess road quality and to what extent these roads influence the distribution of agricultural products. Using simple random sampling of 91 respondents, data were collected through observations, interviews, and questionnaires. The findings indicate that improved roads enhance market access, technology adoption, availability of production inputs, and production incentives. The most significant improvement is in transportation efficiency. Overall, production center roads positively impact farmers’ productivity and income by improving accessibility, reducing costs, and strengthening agricultural supply chains.